ANALISIS FUNGSI TINDAK TUTUR EKSPRESIF PADA “FILM SATU KAKAK 7 KEPONAKAN KARYA ARSWENDO ATMOWILOTO” - Eka Kurniati Eka Kurniati; Khermarinah; Welti Wediati (JIBS : JURNAL ILMIAH BAHASA DAN SASTRA, 2026)
This study aims to analyze the role of expressive speech acts in the film Satu Kakak Tujuh Keponakan. Expressive speech acts are utterances used by speakers to convey or demonstrate psychological states, emotions, and attitudes regarding a specific situation or event. This study employs a descriptive qualitative method. The research data consist of dialogues between characters in the film Satu Kakak Tujuh Keponakan, specifically utterances containing expressive speech acts. Data collection was carried out using the "listen-and-note" method, which involves listening to the film's dialogue and recording utterances relevant to the research focus. The collected data were analyzed by identifying, classifying, and describing the roles of expressive speech acts based on the context of the utterances. The findings are expected to reveal various functions of expressive speech acts employed by the characters such as expressing happiness, sadness, anger, disappointment, fear, gratitude, apologies, and praise, as well as other feelings or attitudes. This study is expected to contribute to the field of pragmatics particularly regarding the application of expressive speech acts in audiovisual media and serve as a reference for similar research.